PERBEDAAN KEMAMPUAN TENAGA PELAKSANA GIZI PUSKESMAS DALAM PENILAIAN PERTUMBUHAN BALITA DI KABUPATEN MINAHASA UTARA DAN KOTA BITUNG - Phembriah S. Kereh; Ana B. Montol; Olga L. Paruntu (Jurnal GIZIDO, 2017)
Based on the results of Riskesdas in 2013, the state of nutrition status, especially for children under five years old in Indonesia, related to stunting problem with TB / U indicator can be described as follows, in Riskesdas 2007 very low prevalence rate of infants (18.0%), 2010 (18.5 %) and in 2013 (18.0%), this prevalence rate has a similarly increasing trend and decline from year to year, as well as for the prevalence of short toddlers, at Riskesda 2007 (18.0%), 2010 ( 17.1%) and in 2013 (19.2%), it shows that the increase of short toddlers in Indonesia is still very high. For growth assessment, children need to be developed in order to know early child growth and this monitoring should be done by trained health personnel in order to obtain data or information on how should the child grow well and follow-up (intervention). The purpose of this research is to know the effect of Growth Monitoring training by using WHO 2005 standard to knowledge, skill of officer in using growth standard of balita.The research type is quasi experiment with pre and post test design one group design. Population in this research is all nutrition officer responsible in monitoring growth of toddler. Processing and data analysis begins with the editing, and coding data to facilitate the process of data entry and then followed by mengentri data on statistical software program, the next stage is to do Pre-test and post-test pre-test results before and after the training obtained the results of knowledge level, attitudes and skills of nutrition workers in puskesmas district in Minahasa Uatara district against the use of WHO 2005 standard, pre-test result for good category knowledge (80%), good category attitude (66,7%) and good category skill (66,7%), (90%) increased by 10%, good attitude category (93.3%) experienced an increase of (26.6%) and good skill category (90%) %) increased (23.3%). Wilcoxon Signed Ranks Test statistic test results to know the difference of knowledge before and after training (p <0.05), there are significant differences (p = 0.000). The result of statistical test of attitude difference before and after training (p <0.05), there were significant differences (p = 0,000) from the test statistic difference of skill before and after training (p <0,005), there was significant difference (p = 0,000).